2015
DOI: 10.1177/0269216315584865
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved carers’ accounts of the end of life and the role of care providers in a ‘good death’: A qualitative study

Abstract: Care providers played a much wider role in social aspects of care at the end of life than previously considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(97 citation statements)
references
References 21 publications
4
91
0
2
Order By: Relevance
“…Moreover, the ‘good death’ experiences reported in this and other papers [25, 33, 34] and more positive stories of satisfaction and accomplishment reported by participants in other studies [8, 1419], underline the importance of knowing that everything went as well as it could have done for the process of adjustment post-death.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, the ‘good death’ experiences reported in this and other papers [25, 33, 34] and more positive stories of satisfaction and accomplishment reported by participants in other studies [8, 1419], underline the importance of knowing that everything went as well as it could have done for the process of adjustment post-death.…”
Section: Discussionsupporting
confidence: 59%
“…Following this, several communication and support needs relating to death and dying were articulated. These included better information on the signs of death in order to facilitate awareness of and preparedness for death [12, 20, 25, 34], along with real time updates on what is happening during the dying process, and what relatives could be doing to help their loved ones at this time. Caregivers and health professionals also described the need for more effective communication and emotional support around EoLC planning and decisions, with detailed discussion at points where the focus of care shifts to prioritising EoLC goals, as evidenced elsewhere [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…The overall aim of this approach to care is to achieve what has been described as the A good death in Western society is considered to be a death with dignity, awareness, peace, adjustment and acceptance (Kehl, 2006, Holdsworth, 2015. However, the conceptualisation of what constitutes a good or bad death is obviously .…”
Section: Palliative Care Philosophymentioning
confidence: 99%
“…Becker et al, 14 however, in a systematic literature review into the role of spirituality in the grieving process and how it may be influenced by characteristics such as age, gender, culture, and religion, concluded that it was not possible to give a definite answer one way or the other due to deficiencies in the methodology of the studies. Holdsworth 15 investigated the endof-life experience of bereaved carers and described six factors contributing to a 'good death': 1) social engagement and connection to identity; 2) carer's characteristics and actions; 3) carer's confidence and ability to care; 4) preparation and awareness of death; 5) presentation of the patient at death; and 6) support for grieving carers after death.…”
Section: Spirituality and 'A Good Death'mentioning
confidence: 99%